The Evaluation of Caring Curriculum for Patients with Stroke in Boromarajonani College of Nursing, Changwat Nonthaburi - Santwanpas, Nichada; Dechpoonyachit, Petchrung; Pandang, Kittikran; Kruttakart, Siriporn; Wanngamwiset, Sudarat (Journal of The Royal Thai Army Nurses, 2020)
This study was aimed to evaluate a caring curriculum for patients with stroke in Boromarajonani College of Nursing, Changwat Nonthaburi using the CIPP framework. The sample was 25 nurses who were trained in the caring curriculum, 25 commanders of nurses who were trained and 25 colleagues of nurses who were trained. Quantitative data was collected including, 1) The CIPP model questionnaire consisting of context, input, process, and the product collected from nurses who were trained in the caring curriculum, and 2) nursing competencies after training questionnaire collected from commanders and colleagues of trained nurses. Qualitative data was collected using a focus group interview with 8 nurses who were trained in a caring curriculum for patients with stroke. Quantitative data were analyzed by percentage, mean and standard deviation, and qualitative data was used by content analysis. The results showed that the quantitative and qualitative findings were consistent. Overall, the results of evaluating a caring curriculum for patients with stroke in Boromarajonani College of Nursing, Changwat Nonthaburi was at a high level ( = 4.17 SD = 0.66). The evaluation of this program in each aspect found that: 1) this program had responded to the policy of health region, 2) the experts have been specialists and the instructional media were ready to use, 3) the process of this training program could guide nurses who were trained to solve of problems in real situations, and 4) nurses who were trained had increased the competencies in caring the patients with stroke and the competencies in searching data.